2021
DOI: 10.1111/bjd.19880
|View full text |Cite|
|
Sign up to set email alerts
|

Risk of skin cancer in new users of thiazides and thiazide‐like diuretics: a cohort study using an active comparator group*

Abstract: Summary Background Case–control studies report a dose‐dependent increased risk of skin cancer in users of hydrochlorothiazide (HCTZ) vs. nonusers. The degree to which other thiazides and thiazide‐like diuretics (TZs) are associated with skin cancer is less certain. Objectives To assess the risk of skin cancer in new users of different TZs compared with new users of calcium channel blockers (CCBs). Methods We conducted a cohort study using a UK primary‐care database (1998–2017), including 271 154 new TZ users [… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
49
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(53 citation statements)
references
References 34 publications
3
49
1
Order By: Relevance
“…Results for KC in BIFAP were generally similar to results from a Danish study, 8 in which high use of HCTZ increased the risk of BCC by 1.3 times (1.1 times in BIFAP) and the risk of SCC by four (1.7 times in BIFAP). Recently, studies from the United Kingdom (UK) also using a primary care database, 11–13 showed similar results. In these studies HCTZ was related to KC too, especially to SCC.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Results for KC in BIFAP were generally similar to results from a Danish study, 8 in which high use of HCTZ increased the risk of BCC by 1.3 times (1.1 times in BIFAP) and the risk of SCC by four (1.7 times in BIFAP). Recently, studies from the United Kingdom (UK) also using a primary care database, 11–13 showed similar results. In these studies HCTZ was related to KC too, especially to SCC.…”
Section: Discussionmentioning
confidence: 71%
“…However, most findings were not directly comparable mainly due to differences in the study methods used and study‐specific limitations. Recently, several studies have found an increased risk of skin and lip cancer related to high cumulative doses of hydrochlorothiazide (HCTZ) in populations from Denmark, 7–9 Iceland, 10 United Kindom 11–13 and Australia, 14 but not in a population from Taiwan 15 …”
Section: Introductionmentioning
confidence: 99%
“…confirm the strongly increased risk of cutaneous squamous cell carcinoma (cSCC) in a cohort study using a UK primary care database. 7 Although, weak associations with melanoma and basal cell carcinoma (BCC) have been observed in some studies, these were not observed in the cohort study of Schneider et al . 7 …”
mentioning
confidence: 97%
“… 7 Although, weak associations with melanoma and basal cell carcinoma (BCC) have been observed in some studies, these were not observed in the cohort study of Schneider et al . 7 …”
mentioning
confidence: 97%
See 1 more Smart Citation